Evaluación financiera de las florícolas de Cayambe y su contribución al objetivo cinco del plan nacional de desarrollo toda una vida - Cedeño Vera, Jhon Mateo (2022)
The purpose of this research was to evaluate the financial situation of the floricultural companies ROSEAMOR, FLORECAL, HOJA VERDE and QUALISA in Cayambe city and their contribution to objective five of the National Development Plan for a Lifetime. Bibliographic, exploratory and field research was used; also, the methods used were deductive, inductive, synthetic, analytical, descriptive and exploratory, among the required techniques were the interview, documentary review, financial analysis and forecast, the guide was used as tools. interview, bibliographic incidence analysis, Ishikawa diagram, 5W+2H matrix and statistical analysis. To obtain the results, four methodological phases were structured, in the first phase the documentary review was carried out to identify the indicators of the study variables, the second phase consisted of the calculation, analysis and forecast of the financial reasons to identify the mercantile risks that surround the floricultural sector, in the third phase the interview was applied to the managers of the entities and then the analysis and variation of the macroeconomic indicators was carried out to identify the contribution of the floricultural sector to objective five mentioned previously and in the fourth phase an improvement plan was designed to counteract the risks detected in the previous phases. This research concludes that the floricultural sector in the period 2017-2020 presented financial problems regarding the level of profitability and indebtedness, however, the floricultural sector contributes to the goals and policies established in objective five of the government plan with respect to the exports and employment.